On the Geometric Transformations and Auxetic Materials - Veturia Chiroiu (Analele Universităţii "Eftimie Murgu" Reşiţa: Fascicola I, Inginerie, 2011)
A new approach to obtain various architectures for auxetic foams by using the property of Helmholtz equation to be invariant under geometric transformations is described in this paper. The versatility of the geometric transformations is illustrated in order to obtain the auxetic version from the conventional foam.